Spatially clustered loci with multiple enhancers are frequent targets of HIV-1 integration - Lucic, Bojana; Wei, Wang; Schmidt, Manfred; Lusic, Marina (Nature Communications, 2019)
HIV-1 recurrently targets active genes and integrates in the proximity of the nuclear pore compartment in CD4+ T cells. However, the genomic features of these genes and the relevance of their transcriptional activity for HIV-1 integration have so far remained unclear. Here we show that recurrently targeted genes are proximal to super-enhancer genomic elements and that they cluster in specific spatial compartments of the T cell nucleus. We further show that these gene clusters acquire their location during the activation of T cells. The clustering of these genes along with their transcriptional activity are the major determinants of HIV-1 integration in T cells. Our results provide evidence of the relevance of the spatial compartmentalization of the genome for HIV-1 integration, thus further strengthening the role of nuclear architecture in viral infection.